Impact of job relocation on marital satisfaction of couples in Ibadan (2015)
This study investigated the impact of job relocation on marital satisfaction. A total of 225 respondents participated in the study made up of 50 police officers, 66 civil servants, 58 soldiers and 51 bankers, 149 males and 66 females. The participants comprise 160 junior staff, 58 senior staff and 7 executives/managers. 60.7% of the respondents agreed that the distance in location affected their sexual satisfaction. 82.7% agreed that it affected their love and affection for their spouse, 67.6% agreed that it affected their communication level, 63.8% agreed that it affected their happiness in marriage, 56.9% agreed that they have conflict on many issues due to distance and 82.7% agreed that it affected their family finances. A significant linear relationship was found between job relocation and all the indices of marital satisfaction (sexual affection, family finance, love and affection, communication level, couples’ happiness, commitment in marriage and conflict between couples). Based on the findings, it was recommended that decision makers should consider the marital implication of organizational decisions of job relocation on the family of employees before making transfer for health and well-being of the members of the family.